1985
DOI: 10.1083/jcb.101.4.1257
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epidermal keratins and filaggrin during human fetal skin development.

Abstract: The major structural proteins of epithelia, the keratins, and the keratin filamentassociated protein, fitaggrin, were analyzed in more than 50 samples of human embryonic and fetal skin by one-dimensional SDS PAGE and immunoblotting with monoclonal and polyclonal antibodies. Companion samples were examined by immunohistochemistry and electron microscopy. Based on structural characteristics of the epidermis, four periods of human epidermal development were identified. The first is the embryonic period (before 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
176
0
4

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(193 citation statements)
references
References 56 publications
(78 reference statements)
13
176
0
4
Order By: Relevance
“…To elucidate the inheritance characteristics of the K10 polymorphism, we used the same PCR technique to amplify the V2 subdomain of the 17 members from one Centre d'Etude du Polymorphisme Humain family (28). A total of four differently sized alleles (labeled [1][2][3][4] of alleles present in the parents (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the inheritance characteristics of the K10 polymorphism, we used the same PCR technique to amplify the V2 subdomain of the 17 members from one Centre d'Etude du Polymorphisme Humain family (28). A total of four differently sized alleles (labeled [1][2][3][4] of alleles present in the parents (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…Besides CK, filament aggregating protein (filaggrin), a histidine-rich phosphorylated basic protein of major constituents of keratohyaline granules, is a marker of terminal differentiation of epidermis (5). No immunohistochemical study of CK and filaggrin in DC has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Cells of the single-layered precursor of the human epidermis produce the same types of CK that are characteristic of simple epithelia, namely CK8, CK18 and CK19 (Dale, Holbrook et al 1985). With the onset of stratification, different cytokeratins are expressed in the basal and suprabasal layers, e.g.…”
Section: Introductionmentioning
confidence: 99%